PERANCANGAN SISTEM INFORMASI AKUNTANSI PEMBELIAN BAHAN BAKU (Studi Kasus : PT. DCM (DADALI CITRA MANDIRI) BANDUNG) - Apriani Puti Purfini; Teguh Prasetyo; S Supriyati (Labkat Press KA FTIK UNIKOM, 2012)
PT DCM (Dadali Citra Mandiri) is manufacturing business which is active in service of telecommunications and construction. Research done at Staff Purchasing, concerning Information System of Accountancy of Raw Material Purchasing. System which walk in company not yet computerized full, and informsai yielded by not yet as according to accountancy standard going into effect in Indonesia. Writer take the title